FOOD ESTATE POLICY REVIEWED FROM ENVIRONMENTAL CRIMINAL LAW - Nasution, Faradila Umaya; Syahrin, Alvi; Suhaidi, Suhaidi (NOMOI Law Review, 2025)
The conditions during the Covid-19 pandemic have made the issue of food security a hot topic of discussion because the government is worried about a food deficit in Indonesia. Not only because of the pandemic, the issue of food security has become a national and even international issue. In an effort to overcome and prevent the food crisis, the government issued a food estate policy as a solution to overcome the food crisis. However, in its implementation, the food estate program was carried out on land such as production forest areas and debt protection. Thus, land acquisition for the program creates new problems for the environment. This study uses a normative legal research method with a regulatory approach. The results of the study show that the food estate program often does not produce results according to expectations. Even in the context of environmental criminal law, the food estate program often violates the neglect of administrative obligations such as violations of permits. So that this program needs to be evaluated and planned carefully before the program is implemented.